(untitled) (Eurasian Journal of Philology Science and Education, 2016)
The article is devoted to ballet performances based on William Shakespeare’s dramaturgy, produced on the stages of theaters of ballet in Kazakhstan. A brief overview of the history of these performances has been presented, and the author pays main attention to performances staged recently in 2010 and 2014. Namely, the ballets «Romeo and Juliet» produced at Abay SATOB by the eminent choreographer Yuri Grigorovich and at the stage of «Astana Opera» theater by French choreographer S. Jude. During the analysis, the author compares new productions with the ballet of Lavrovsky which is the most famous in the world’s ballet theater, in which the legendary G. Ulanova have danced. Performance is produced in the style of a large, but at the same laconic performance. The love of two young creatures is the most important thing for the choreographer, while the circumstances and entourage of this love story retreat to the second plan. Therefore, the ballet has a timeless character and thus is perceived as a modern performance.